The Simulation of Combustion Characteristics from Diesel Fuel and Biodiesel in Different Engine Rotation - Bhikuning*, Annisa; Irhashi, Zidni Rizki; Aldebaran, Daniel (Graduate School of Universitas Syiah Kuala, 2022)
The combustion characteristics of fuel are important to understand. Diesel engines can ruin by using fuel from diesel and biodiesel. The characteristics between biodiesel and diesel fuel are different. Diesel fuel has low viscosity, high volatility, and low density, and the cetane number is around 48. However, biodiesel has high density, low volatility, high viscosity, and higher cetane number than diesel fuel. Using biodiesel can reduce the particulate matter from the engine. This happened because biodiesel has high oxygen content and can reduce emissions. These are some advantages of using biodiesel in diesel engines. In this research, the simulation of the combustion characteristics was investigated by diesel-rk simulation. The fuels are diesel and biodiesel made from soybean methyl ester (SME). In this simulation, pure diesel fuel (DF), SME100, SME20 (20%SME blends to 80%DF), and SME40 (40%SME blends to 60%DF) are investigated. The combustion was set up with 1500, 1800, and 2000 rpm. The results show that DF has higher Specific Fuel Consumption (SFC) in all engine rotations than SME. Moreover, the NO2 emission from DF is lower than SME. However, the particulate matter in SME40 can reduce up to 16.1% compared to DF. Moreover, the higher the engine rotates, the fewer emissions from NO2 and PM from SME20, SME40, and DF can be reduced. It can be confirmed that the higher rotation in the engine can decrease its emissions. In addition, biodiesel can be replaced with diesel fuel, which is environmentally friendly.